Analisis Kerugian Ekonomis Pada Model Peramalan Permintaan Produk Air Minum Dalam Kemasan (Studi Kasus Pada Produk AMDK Aiso dan Ayudes) - J.M Tupan (Industrial Engineering Study Program, Pattimura University, 2015)
Forecasting always provide different results to its actual values, that are negative or positive difference. Economically, these dissimilarities have impact on losses. This article aims to (1) establish a forecasting model to forecast the demand of packaged drinking water (AMDK) based on the actual data pattern of Aiso and Ayudes; (2) establish a partial forecasting model according to performance criteria of model; and (3) compare the expectation value of economic losses among each model. Result of study presents Single Exponential Smoothing as the chosen model with lower error to forecast AMDK demand. It also shows that the lower expectation of economic losses for AMDK Aiso is provided by Trend Analysis model, while the highest expectation yielded by Moving Average and Single Exponential Smoothing model. The lower expectation of economic losses for AMDK Ayudes is provided by Trend Analysis model, while the highest expectation yielded by Double Exponential Smoothing model. The minimum expectations of economic losses produced by Trend Analysis Model are Rp. 229.781.833 (AMDK Aiso) and Rp.279.120.911 (AMDK Ayudes).